High intensity training at altitude for team sports athletes - Faiss, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Athletes seem compelled to include some forms of altitude training in their preparation expecting additional performance gains compared to equivalent training at sea-level. For long, they spent weeks at altitude to enhance oxygen delivery to the muscles with "live hightrain high" or "live high-train low" altitude camps. For the last twenty years, the development of hypoxic facilities largely facilitated various forms of "live low-train high" (LLTH) methods where athletes live at or near sea level but train in hypoxia. Until recently, most LHTL strategies involving any form of continuous or intermittent training in hypoxia were classified under the "intermittent hypoxic training" (IHT) denomination. A comprehensive analysis IHT studies highlights only poor extra benefits of adding a hypoxic stimulus for sea-level performance improvement despite positive molecular adaptations observed after various IHT modalities (2). To overcome some limitations hindering additional performance benefits with hypoxia, our research group recently developed novel maximal intensity exercise protocols in hypoxia, e.g., epeated sprint training in hypoxia (RSH) (3), incidentally well adapted to team sports athletes. Fundamental mechanisms (likely with positive adaptations in the behaviour of fast-twitch fibres) underpin the efficacy of RSH and differentiate it from IHT in the updated panorama of contemporary altitude training methods (5). With RSH, performing `all-out` efforts in hypoxia may provide additional activation of anaerobic and neuromuscular pathways beyond that observed in normoxia. The role of exercise intensity per se in the training induced responses in hypoxia should now be recognized and RSH may indeed potentiate the effects of adding a hypoxic stress to a training stimulus by challenging at most the adaptive mechanisms of the tissue working in hypoxia to promote subsequent performance gains in normoxia (4). Although there is no consensus on best-practice strategies with altitude training for team sports, adding RSH during an altitude training camp may trigger most adaptive mechanisms for improved team performance (1). Although numerous factors influence match running performance and overall game results in team sports, individual player performance improvement is crucial. Proposing RSH in team sports may thus boost players` physical performance, prepare their organism to subsequent more sports specific training and potentially delay premature in-match fatigue.